Government Regulations in Digital Banking: Bibliometric Studies From 2017 – 2021 - Oskar Vitriano; Resi Pranacitra; Gunawan Nachrawi; Kiki Pranowo (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
As newly developing trends in the finance sector, digital banking has gained significant research interest. This research aimed to explore the role of government regulations in Digital Banking. The authors see that research on the Government regulation on Digital Banking are still limited. The paper uses a bibliometric analysis approach to summarize the trends of government regulations to digital banking. The research was limited to Scopus journals published during the 2017-2021 period. The results show that the number of government regulation research is low and keeps increasing to guard the development of digital banking to its users.